2021
DOI: 10.3390/biom11091309
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation Abnormalities in Renal Pathology of Chronic Kidney Disease: The Interplay between Blood Cells and Soluble Factors

Abstract: Coagulation abnormalities in renal pathology are associated with a high thrombotic and hemorrhagic risk. This study aims to investigate the hemostatic abnormalities that are related to the interaction between soluble coagulation factors and blood cells, and the effects of hemodialysis (HD) on it, in end stage renal disease (ESRD) patients. Thirty-two ESRD patients under HD treatment and fifteen healthy controls were included in the study. Whole blood samples from the healthy and ESRD subjects were collected be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…This indicates a hypo‐fibrinolytic state and pro‐thrombotic risk. Pavlou et al 21 also found pre‐HD PAI levels to be much greater than those of the normal cohort. PAI levels decreased post‐HD but remained significantly greater than those of the controls.…”
Section: Haemostatic Alterations In Kidney Failurementioning
confidence: 91%
See 2 more Smart Citations
“…This indicates a hypo‐fibrinolytic state and pro‐thrombotic risk. Pavlou et al 21 also found pre‐HD PAI levels to be much greater than those of the normal cohort. PAI levels decreased post‐HD but remained significantly greater than those of the controls.…”
Section: Haemostatic Alterations In Kidney Failurementioning
confidence: 91%
“…Nonetheless, this study concluded that both factors increase greatly and uniformly with HD and HDF. Pavlou et al 21 measured several coagulation factors pre‐ and post‐HD. Pre‐HD, fibrinogen, FXIII, VWF and FVIII levels were much greater than those of the normal population and further increased post‐HD.…”
Section: Haemostatic Alterations In Kidney Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular ROS (iROS) and calcium (iCa 2+ ) levels were measured by flow cytometry as previously described ( Pavlou et al, 2021 ). For the detection of cleaved caspase-3 (RBC caspase-3), red blood cells were washed three times with phosphate-buffered saline solution (PBS) and were resuspended in PBS at a concentration of 4% Hct.…”
Section: Methodsmentioning
confidence: 99%
“…Avoiding the serious consequences caused by excessive blood loss and wound infection has always been the focus of clinical medical research. It can be seen from the above that electrospinning nanofibers are a good choice with structural and performance advantages [ 130 , 131 , 132 , 133 , 134 ]. Electrospinning of poly(amino acids) with high biocompatibility and loading of drugs or active substances with anti-inflammatory, antibacterial, and hemostatic functions can obtain electrospun nanofibers with good medical effects and sustained drug release therapeutic effects [ 135 , 136 , 137 , 138 , 139 ].…”
Section: Applicationmentioning
confidence: 99%